Bolaño en el camino: El viaje como búsqueda de identidad en Los detectives salvajes - Gustavo Pierre Herrera López (Confluenze, 2012)
What are looking for the main characters of Los detectives salvajes by Roberto Bolaño in the desert? The following essay proposes a reading of travels in Bolaño’s work, as journeys on which there are a research of identity denied by the ruling culture; the journey to the desert are presented as the transition moment between the modern condition of the characters and the postmodern condition, and the traveler like the person who reads his life like a fiction.